2014
DOI: 10.1504/ijmrm.2014.059697
|View full text |Cite
|
Sign up to set email alerts
|

Move Odyssey in China: rural-urban migration and subsequent relocation in cities

Abstract: It may be a long series of wanderings or adventures filled with notable experiences and hardships that a rural person in current China migrates into urban area and attempts to relocate in it. Hukou conversion, family separation, and job opportunity become the three main barriers for rural migrants transform into urban citizen. Academic identification has verified there is full of risks for the expectations and consequences of residential mobility in China as to a rural family. An empirical exploration is neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Han [84] conducted a regression analysis of economic variables, including years prepared for moving between rural and urban areas, and identified the hukou conversion, family separation, and job opportunity as the main barriers that prevent rural migrants from transforming into urban citizens. However, the study has demonstrated that rural migration is not only restricted by administrative regulations, since people continue migrating even under the hukou registration system.…”
Section: Discussionmentioning
confidence: 99%
“…Han [84] conducted a regression analysis of economic variables, including years prepared for moving between rural and urban areas, and identified the hukou conversion, family separation, and job opportunity as the main barriers that prevent rural migrants from transforming into urban citizens. However, the study has demonstrated that rural migration is not only restricted by administrative regulations, since people continue migrating even under the hukou registration system.…”
Section: Discussionmentioning
confidence: 99%